Moth hair in cornea in a case of seasonal hyperacute panuveitis - Ranju Kharel (Sitaula) (Indian Journal of Ophthalmology, 2020)
Seasonal Hyperacute Panuveitis (SHAPU) is a seasonal and cyclic uveitic disease reported only from Nepal occurring every odd year. Untreated eyes go blind and phthisis within a week. Circumstantial evidence for the role of moths has been reported earlier. Herein for the first time, we describe a SHAPU case in a healthy young Nepalese patient where the exposure to white moth was followed by the development of the uveitis and the moth hair particles was detected in the corneal and presence was confirmed with anterior segment optical coherence topography.